2006
DOI: 10.1111/j.1471-4159.2006.03668.x
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine‐induced endoplasmic reticulum protein (Herp) is up‐regulated in sporadic inclusion‐body myositis and in endoplasmic reticulum stress‐induced cultured human muscle fibers

Abstract: Herp is a stress-response protein localized in the endoplasmic reticulum (ER) membrane. Herp was proposed to improve ER-folding, decrease ER protein load, and participate in ERassociated degradation (ERAD). Intra-muscle-fiber ubiquitinated multiprotein-aggregates containing, among other proteins, either amyloid-b (Ab) or phosphorylated tau are characteristic of sporadic inclusion-body myositis (s-IBM). ER stress and proteasome inhibition appear to play a role in s-IBM pathogenesis. We have now studied Herp in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(82 citation statements)
references
References 44 publications
1
81
0
Order By: Relevance
“…STIP1, a member of HSP70-HSP90 organizing protein (HOP) family which functions as a cochaperone that reversibly links together HSP70 and HSP90 protein chaperones (Odunuga et al 2004) and prostaglandin E synthase 3 (PTGES3) which functions as a cochaperone, along with HSP90 were also upregulated. HS results in an increase in cytotoxic protein in the endoplasmic reticulum (ER), HERPUD1 which was found to be upregulated in this study functions in processing and degradation of these cytotoxic protein by participating in ER-associated degradation (ERAD) (Nogalska et al 2006). Foldases are required for protein folding (Nagradova 2007); they catalyze protein folding by isomerizing peptide bonds with peptidyl-prolyl 4 hydroxylase which results in rearrangement of disulfide bonds (Wilkinson and Gilbert 2004); in this study, protein disulfide isomerase family A member 3 (PDIA3) was found to be elevated in response to HS.…”
Section: Heat Stress Resulted In the Activation Of Heat Shock Factorsmentioning
confidence: 99%
“…STIP1, a member of HSP70-HSP90 organizing protein (HOP) family which functions as a cochaperone that reversibly links together HSP70 and HSP90 protein chaperones (Odunuga et al 2004) and prostaglandin E synthase 3 (PTGES3) which functions as a cochaperone, along with HSP90 were also upregulated. HS results in an increase in cytotoxic protein in the endoplasmic reticulum (ER), HERPUD1 which was found to be upregulated in this study functions in processing and degradation of these cytotoxic protein by participating in ER-associated degradation (ERAD) (Nogalska et al 2006). Foldases are required for protein folding (Nagradova 2007); they catalyze protein folding by isomerizing peptide bonds with peptidyl-prolyl 4 hydroxylase which results in rearrangement of disulfide bonds (Wilkinson and Gilbert 2004); in this study, protein disulfide isomerase family A member 3 (PDIA3) was found to be elevated in response to HS.…”
Section: Heat Stress Resulted In the Activation Of Heat Shock Factorsmentioning
confidence: 99%
“…9,10 Previously, in various species including mammals, ER stress was reported to induce macroautophagy, as evidenced by increased LC3-II, [51][52][53][54] putatively to eliminate misfolded/unfolded proteins accumulated in the ER lumen. 54 In agreement with those reports, ER stress induced in our primary cultures of human muscle increased macroautophagy as reflected by the LC3-II increase and phosphorylated p70S6 kinase decrease; however, concurrently, ER stress impaired enzymatic activities of the lysosomal proteases cathepsin D and B.…”
Section: Discussionmentioning
confidence: 99%
“…Each experiment was performed on at least five different culture sets, each established from satellite cells derived from a different muscle biopsy sample. Twelve to 18 days after fusion of myoblasts, well differentiated myotubes were exposed for 24 hours to either i) an established ER stress inducer tunicamycin, which is an Nglycosylation inhibitor 29 (4 g/ml; Sigma-Aldrich) that in our previous studies was shown to induce ER stress and its consequences, 10,30,31 ii) an irreversible proteasome inhibitor epoxomicin 8,26,32 (1 mol/L; BIOMOL Research Laboratories, Plymouth Meeting, PA), iii) bafilomycin A1, an inhibitor of lysosomal V-ATPase, causing an increase of lysosomal pH 33 and inhibiting activities of cathepsins (25 nmol/L; Sigma-Aldrich), or iv) chloroquine (20 mol/L; Sigma-Aldrich) for 24 and 48 hours, a lysosomotropic agent raising lysosomal pH 33 and inhibiting activities of cathepsins. After these various treatments, cultures were processed for immunoblots as described previously 9,10,26,30 or measurement of enzymatic activities as above for muscle biopsy samples.…”
Section: Cultured Human Muscle Fibersmentioning
confidence: 99%
“…HERP (homocysteine-induced ER stress protein) is a chaperone-like protein that is strongly upregulated by ER stress (Kokame et al, 2001;Schröder and Kaufman, 2005) and then rapidly degraded (Hori et al, 2004;Kim et al, 2008;Sai et al, 2003). Unlike other stress-induced cytoplasmic chaperones, HERP is an integral membrane protein with both its N-and C-termini facing the cytoplasm (Nogalska et al, 2006;Sai et al, 2002). The function of HERP is not fully understood, but accumulating evidence suggests that it has an essential role in ER-membrane-associated protein degradation (ERAD), which functions to retrotranslocate ubiquitylated proteins from the ER to proteasomes for degradation (Schulze et al, 2005).…”
Section: Introductionmentioning
confidence: 99%